Mechanism of Hip Arthropathy in Ankylosing Spondylitis: Abnormal Myeloperoxidase and Phagosome - Yu, Chaojie; Zhan, Xinli; Liang, Tuo; Chen, Liyi; Zhang, Zide; Jiang, Jie; Xue, Jiang; Chen, Jiarui; Liu, Chong (Frontiers in Immunology, 2021)
Background The pathogenesis of Ankylosing spondylitis (AS) has not been elucidated, especially involving hip joint disease. The purpose of this study was to analyze the proteome of diseased hip in AS and to identify key protein biomarkers. Material and Methods We used label-free quantification combined with liquid chromatography mass spectrometry (LC–MS/MS) to screen for differentially expressed proteins in hip ligament samples between AS and No-AS groups. Key protein was screened by Bioinformatics methods. and verified by in vitro experiments. Results There were 3,755 identified proteins, of which 92.916% were quantified. A total of 193 DEPs (49 upregulated proteins and 144 downregulated proteins) were identified according to P < 0.01 and Log|FC| > 1. DEPs were mainly involved in cell compartment, including the vacuolar lumen, azurophil granule, primary lysosome, etc. The main KEGG pathway included Phagosome, Glycerophospholipid metabolism, Lysine degradation, Pentose phosphate pathway. Myeloperoxidase (MPO) was identified as a key protein involved in Phagosome pathway. The experiment of siRNA interfering with cells further confirmed that the upregulated MPO may promote the inflammatory response of fibroblasts. Conclusions The overexpression of MPO may contribute to the autoimmune inflammatory response of AS-affected hip joint through the phagosome pathway.